Scope of the program families in action as policy public in colombia (2013)
In Colombia , the compensation funds were inspired by Decree 118 of 1957 which regulates the Family Grant , have enjoyed sound and outreach program were consolidated as an important alternative to the State in terms of attendance and social provision for the benefit of the class Country worker with so much inequality , since employment, social security and welfare of the communities was clearly state responsibility , a task that has not been easy to fulfill. The work of the compensation funds was highly questionable, it was suggested that social inequalities occasioned benefit only workers affiliated companies . However, these organizations demonstrated their ability and service to the underprivileged providing a welfare workers and their families, both in money and in kind (through school supplies, scholarships, medicines, food, access to health services recreation , culture, among others ... ) .